Analisis Efisiensi Pemulihan Biaya Penuh Dalam Meningkatkan Pendapatan (Pada Perusahaan Daerah Air Minum Kabupaten Banyuwangi) - Yosky Margaretha Claudia Putri; Diyah Probowulan; Astrid Maharani (Ecobuss, 2018)
ABSTRACT The aims of this study are to analyze the efficiency of Full Cost Recovery to increase revenue. This research was conducted at PDAM Banyuwangi. The type of this research is descriptive by quantitative data. The type of data is used subject and documentary. The data source is used in primary data. Data collection techniques which used in this study by using interview and literature study methods. Data analysis technique in this research is used analysis of variance of budget and production cost. The results of the research show that the cost incurred PDAM Banyuwangi more profitable (favorable) despite the increase in costs each year that causes the difference in each year. Keywords: Analysis of Variance, Efficiency, Full Cost Recovery, Revenue.